2006
DOI: 10.1002/jcb.20869
|View full text |Cite
|
Sign up to set email alerts
|

The exonuclease ISG20 mainly localizes in the nucleolus and the Cajal (Coiled) bodies and is associated with nuclear SMN protein‐containing complexes

Abstract: We have previously shown that ISG20, an interferon (IFN)-induced gene, encodes a 3' to 5' exoribonuclease member of the DEDD superfamily of exonucleases. ISG20 specifically degrades single-stranded RNA. In this report, using immunofluorescence analysis, we demonstrate that in addition to a diffuse cytoplasmic and nucleoplasmic localization, the endogenous ISG20 protein was present in the nucleus both in the nucleolus and in the Cajal bodies (CBs). In addition, we show that the ectopic expression of the CBs sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 89 publications
3
29
0
Order By: Relevance
“…2A), notably Cajal bodies (Fig. 2B), contrary to ISG20 (40). These observations confirm that ISG20L2 is a nucleolar protein.…”
Section: In Silico Prediction Of Potential Functional Domains Of Isg2supporting
confidence: 72%
“…2A), notably Cajal bodies (Fig. 2B), contrary to ISG20 (40). These observations confirm that ISG20L2 is a nucleolar protein.…”
Section: In Silico Prediction Of Potential Functional Domains Of Isg2supporting
confidence: 72%
“…It has been shown that this exonuclease is a component of the nuclear PML body (21,27). Previous studies demonstrated that ISG20 expression confers resistance to the infection of various RNA viruses, including VSV and human immunodeficiency virus, but not DNA viruses, such as adenoviruses (19,20,68).…”
Section: Discussionmentioning
confidence: 99%
“…ISG20 is a 3Ј-to-5Ј exonuclease with a strong preference for single-stranded RNA and minor activity toward single-stranded DNA (51). According to the bioinformatic analysis and recently published crystal structural data, ISG20 belongs to the DEDD superfamily of 3Ј-to-5Ј exonucleases that is defined by four conserved acidic residues, three aspartates (D) and one glutamate (E), distributed among three separate sequence motifs (Exo I to III) (19,21,34,74). Previous studies demonstrated that replacement of Asp96 in Exo II with a glycine inactivates the enzymatic activity of ISG20 (19).…”
Section: Pkrmentioning
confidence: 99%
“…However, ISG20 can also be expressed at high levels in peripheral blood leukocytes, lymphoid tissues (such as spleen or thymus), the colon, and the lungs without exogenous IFN treatment (2). When the location of ISG20 protein was assessed immunohistochemically in human HeLa and lymphoblastoid Daudi cells, diffuse cytoplasmic and nucleoplasmic localization was observed, but ISG20 also appeared in the nucleus, including the nucleolus and Cajal bodies (CBs) (14). Further, electron microcopy analysis revealed that ISG20 was principally concentrated in the dense fibrillar component of the nucleolus, the major site for rRNA processing (14).…”
Section: Expressionmentioning
confidence: 99%
“…When the location of ISG20 protein was assessed immunohistochemically in human HeLa and lymphoblastoid Daudi cells, diffuse cytoplasmic and nucleoplasmic localization was observed, but ISG20 also appeared in the nucleus, including the nucleolus and Cajal bodies (CBs) (14). Further, electron microcopy analysis revealed that ISG20 was principally concentrated in the dense fibrillar component of the nucleolus, the major site for rRNA processing (14). Similarly, laser confocal microscopy detected porcine ISG20 primarily in the nucleus, with only a small amount in the cytoplasm (15).…”
Section: Expressionmentioning
confidence: 99%